IKK is a therapeutic target in KRAS-Induced lung cancer with disrupted p53 activity - Bassères, Daniela S. (Impact Journals LLC, 2014)
Activating mutations in KRAS are prevalent in cancer, but therapies targeted to oncogenic RAS have been ineffective to date. These results argue that targeting downstream effectors of RAS will be an alternative route for blocking RAS-driven oncogenic pathways. We and others have shown that oncogenic RAS activates the NF-κB transcription factor pathway and that KRAS-induced lung tumorigenesis is suppressed by expression of a degradation-resistant form of the IκBα inhibitor or by genetic deletion of IKKβ or the RELA/p65 subunit of NF-κB. Here, genetic and pharmacological approaches were utilized to inactivate IKK in human primary lung epithelial cells transformed by KRAS, as well as KRAS mutant lung cancer cell lines. Administration of the highly specific IKKβ inhibitor Compound A (CmpdA) led to NF-κB inhibition in different KRAS mutant lung cells and siRNA-mediated knockdown of IKKα or IKKβ reduced activity of the NF-κB canonical pathway. Next, we determined that both IKKα and IKKβ contribute to oncogenic properties of KRAS mutant lung cells, particularly when p53 activity is disrupted. Based on these results, CmpdA was tested for potential therapeutic intervention in the Kras-induced lung cancer mouse model (LSL-Kras(G12D)) combined with loss of p53 (LSL-Kras(G12D)/p53(fl/fl)). CmpdA treatment was well tolerated and mice treated with this IKKβ inhibitor presented smaller and lower grade tumors than mice treated with placebo. Additionally, IKKβ inhibition reduced inflammation and angiogenesis. These results support the concept of targeting IKK as a therapeutic approach for oncogenic RAS-driven tumors with altered p53 activity.